The Sociological Implications of the Presence of Foreign Workers for Southeast Sulawesi Resident - Affan, Ibnu; Rahmadani, Gema (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2025)
One of the areas targeted for foreign workers entering Indonesia is the Southeast Sulawesi Province (Southeast Sulawesi). According to data from the Southeast Sulawesi Manpower and Transmigration Office (Disnakertrans), it was recorded that there were approximately 3,200 foreign workers working in Southeast Sulawesi, dominated by foreign workers from China. For this reason, the Provincial Government of Southeast Sulawesi always provides guidance and supervision of foreign workers, by providing them with an understanding of customary and cultural conditions. At first the arrival of these foreign workers caused turmoil and rejection from the community. However, the government has explained that the foreign workers who come to Southeast Sulawesi are workers who have special expertise in order to accelerate the construction of smelters. A local workforce will be prepared to assist these TKA, so that there will be a transfer of knowledge. If the local workforce is able to understand the technology, the next operation will be handed over to the local workforce. After the community understood the situation of this problem, finally it began to appear that the community's acceptance of TKA.